TUNTUTAN HAK DALAM PENEGAKAN HAK LINGKUNGAN (ENVIRONMENTAL RIGHT) - Bestian Adha; Erwin Syahruddin (The Juris, 2022)
Claiming rights is a way to obtain protection for the rights of a person or legal entity granted by the court to prevent vigilante action (eigenrichhting). In his life humans choose several rights to defend including: first civil and political rights, second economic and social rights and the third is the right of solidarity or brotherhood. One type of human rights that has not been elaborated on is the right to the environment. Environmental rights are one of the rights that we need to fight for, considering that the environment cannot fight for its own interests because it is inanimate (unable to speak) so that other parties are needed to fight for it. It is necessary to expand access to justice in enforcing environmental law considering that filing rights claims in civil procedural law in Indonesia only relies on the provisions of the Het Herzeine Indonesich Reglement (HIR). such as class action, legal standing and citizen lawsuit. This paper will discuss the different characteristics of each of these rights claims in terms of environmental law enforcement. A class action lawsuit is a mechanism for filing claims for rights filed by representatives of groups fighting for their interests and their groups. An NGO lawsuit or legal standing is a mechanism for filing a lawsuit by an NGO, the lawsuit is filed if it conflicts with the articles of association of the NGO. Citizen lawsuit is a lawsuit filed by one or more citizens on behalf of all citizens addressed to the State.